Perbedaan Hasil Belajar Mahasiswa Bekerja Dengan Tidak Bekerja - siti jamiyati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2019)
This research aims to determine the differences in academic achievement between working and non-working students at the Faculty of Tarbiyah, IAIN Sorong, class of 2023. The background of the study lies in the increasing number of students who juggle their studies with part-time jobs, which may affect their academic performance. This study employed a quantitative approach with a causal-comparative design. The population consisted of 2023 cohort students, and a purposive sampling technique was used to select 16 students divided equally into two groups: working and non-working. Data collection used structured questionnaires to determine employment status and academic transcripts for learning outcomes (measured by GPA). Data analysis was conducted using an independent sample t-test with SPSS software. The findings indicate that there is no statistically significant difference in the GPA between students who work and those who do not, as evidenced by a significance value of 0.960 (p > 0.05). Although non-working students had a slightly higher average GPA (3.7183) than working students (3.7117), the difference was negligible. The study concludes that employment status alone does not significantly affect student academic achievement.